Workplace stress, support and stress management strategies for healthier lifestyles among healthcare workers in Ethiopia - Zewdie Birhanu; Habtamu Mekonen; Reginald A. Kavishe; Lars Lien; Lena Skovgaard Andersen; Declare L. Mushi; Tania Aase Dræbel; Gudina Terefe Tucho (PLoS ONE, 2026)
Introduction Workplace stress is an ongoing global and local challenge in healthcare, driven by high demands, long hours, and emotional strain, requiring urgent attention to safeguard workers’ well-being and ensure quality care. Objective This study assessed workplace stress, support systems, and coping strategies among healthcare professionals in Jimma Zone, Ethiopia Methods A facility based cross sectional study was conducted in Jimma Zone, Ethiopia, in August 2023. A total of 496 healthcare professionals from five different hospitals were randomly selected to participate in the study. Various validated scales, including the Workplace Stress Scale (WSS), Workplace Support for Health Scale (WSHS), and Oslo Social Support Scale (OSSS-3) were used to assess the participants’ stress levels, social support systems, and their utilization of coping strategies. The data analysis involved descriptive statistics and ordinal logistic regression techniques. Results Results showed that 53% of healthcare workers experienced stress, with 25% reporting low, 16% moderate, and 12% severe stress. Positive workplace support for a healthier life was reported by 54% of respondents. Stress levels were significantly linked to factors like qualifications, facility type, and salary level (p < 0.05). Female workers had slightly lower stress odds than males. Workers aged 30–39 and 50–59 had lower odds of stress compared to those under 30. Higher income and working in primary hospitals were associated with reduced stress odds compared to lower income and referral hospitals. Conclusions This study found considerable workplace stress driven by individual, organizational, and external factors, calling for targeted interventions like stress management training and resilience building programs to enhance health workers’ coping skill and improve healthcare environments in Ethiopia.